Prehranska in presnovna obravnava pacientov po COVID-19 z odpovedjo dihanja - Majdič, Neža (Rehabilitacija (Ljubljana), 2021)
Background: Patients after COVID-19 infection and respiratory failure with critical illness myopathy and/or neuropathy are at high nutritional risk and at high risk for malnutrition-related complications. Our aim was to determine the proportion of nutritional disorders in these patients, the frequency of associated conditions and changes in laboratory parameters that affect the nutritional and metabolic status, and to analyse values of body composition parameters. Methods: The empirical prospective study included 30 patients after COVID-19 infection and respiratory failure with critical illness myopathy and/or neuropathy, who were hospitalized in the Department for rehabilitation of patients after injuries, with peripheral nervous disorders and rheumatoid disease at the University Rehabilitation Institute in Ljubljana from the beginning of November 2020 until mid-March 2021. Body composition parameters (phase angle, fat-free mass index, dry lean mass and hydration status) and laboratory parameters (markers of inflammation, albumin, vitamin D, anaemia) were monitored. We diagnosed nutritional disorders, set the nutritional treatment plan and performed continuous monitoring. Results: Twenty-nine patients out of thirty met GLIM criteria for malnutrition, twenty-five of whom were severely malnourished (Grade 2). Most patients lost 11-15% of body mass during acute hospitalization, some even more than 25%. Nineteen patients (63%) had associated conditions that affect the nutritional and metabolic status, mostly pressure sores. All patients had low phase angle (PA) at admission. Improvement in PA during rehabilitation was statistically significant, but the values were still below the fifth percentile of population. Conclusion: The results indicate that the majority of patients are malnourished upon admission to rehabilitation, so an active screening for malnutrition is necessary. Optimal nutritional and metabolic management can contribute to a better rehabilitation outcome.
Keywords: COVID-19; fazni kot; malnutrition; Nutrition Therapy; nutritional support; odpoved dihanja; phase angle; podhranjenost; prehranska podpora; rehabilitacija; Rehabilitation; respiratory failure